Bacteria Cultivated From Sponges and Bacteria Not Yet Cultivated From Sponges—A Review - Dat, Ton That Huu; Steinert, Georg; Cuc, Nguyen Thi Kim; Smidt, Hauke; Sipkema, Detmer (Frontiers in Microbiology, 2021)
The application of high-throughput microbial community profiling as well as ‘omics’ approaches unveiled high diversity and host-specificity of bacteria associated with marine sponges, which are renowned for their wide range of bioactive natural products. However, exploration and exploitation of bioactive compounds from sponge-associated bacteria have been limited because the majority of the bacteria remains recalcitrant to cultivation. In this review, we i) discuss recent/novel cultivation techniques that have been used to isolate sponge-associated bacteria, ii) provide an overview of bacteria isolated from sponges until 2017 and the associated culture conditions and identify the bacteria not yet cultured from sponges, and iii) outline promising cultivation strategies for cultivating the uncultivated majority of bacteria from sponges in the future. Despite intensive cultivation attempts, the diversity of bacteria obtained through cultivation remains much lower than that seen through cultivation-independent methods, which is particularly noticeable for those taxa that were previously marked as ‘sponge-specific’ and ‘sponge-enriched’. This poses an urgent need for more efficient cultivation methods. Refining cultivation media and conditions based on information obtained from metagenomic datasets and cultivation under simulated natural conditions are the most promising strategies to isolate the most wanted sponge-associated bacteria.